Phaeodaria: An Important Carrier of Particulate Organic Carbon in the Mesopelagic Twilight Zone of the North Pacific Ocean. Issue 8 (21st August 2019) - Ikenoue, Takahito; Kimoto, Katsunori; Okazaki, Yusuke; Sato, Miyako; Honda, Makio C.; Takahashi, Kozo; Harada, Naomi; Fujiki, Tetsuichi
Abstract: Phaeodaria, which comprise one group of large, single‐celled eukaryotic zooplankton, have been largely ignored by past marine biological studies because Phaeodaria and their delicate skeletons are liable to collapse. As a result, collection and quantification of specimens are difficult, and seasonal changes of phaeodarian abundance have not been thoroughly studied. The transport of biogenic elements by sinking phaeodarians has been estimated for only a few representative species. Sinking particles >1 mm in size and swimmers have traditionally been excluded when estimating sinking particle fluxes. The focus of this study is the large number of phaeodarians among the >1‐mm sinking particles collected in the western North Pacific from June 2014 to July 2015. Careful sorting by microscopic examination and chemical analyses revealed that phaeodarians accounted for up to about 10% of the organic carbon in all sinking particles and accounted for a mean of 33% of the organic carbon in the >1‐mm sinking particles. The high‐standing stocks of phaeodarians at depths of 150–1, 000 m in the mesopelagic twilight zone suggested that particles sinking from the euphotic zone as aggregates and fecal pellets can be efficiently exported to the deep sea by the ballasting effect of large phaeodarian particles rich in organic carbon. Key Points: Phaeodarians accounted for up to ~10% of the organic carbon in all sinking particles (both >1 and <1 mm in size) Phaeodarians accounted for a mean of 33% of the organic carbon in the >1‐mm sinking particles Phaeodarians can contribute to the enlargement and aggregation of sinking particles in the mesopelagic carbon cycle